2010
DOI: 10.1007/s10152-010-0193-4
|View full text |Cite
|
Sign up to set email alerts
|

Macroalgal fouling on the intertidal mole crab Emerita analoga facilitates bird predation

Abstract: In this work, we studied the effects of predation by birds on the intertidal mole crab Emerita analoga fouled by macroalgae in a sandy beach of central Peru (11°S). The epibiosis affected mostly the larger animals, especially adult females. Epibiosis prevalence for the entire intertidal population was relatively low (1-2%), however, within the size range affected by epibiosis in the intertidal zone (18-23 mm in carapace length), 20-38% of the animals were fouled. Focal observations of birds showed that fouled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
0
6
0
1
Order By: Relevance
“…obs. ; also see Hidalgo et al, 2010;MacGinitie, 1938). Large females may be better equipped to burrow in coarse sand despite strong wave action than smaller crabs (including males).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…obs. ; also see Hidalgo et al, 2010;MacGinitie, 1938). Large females may be better equipped to burrow in coarse sand despite strong wave action than smaller crabs (including males).…”
Section: Discussionmentioning
confidence: 99%
“…If slower burrowing increases vulnerability to bird predators, then infected crabs may be more likely to be captured by these definitive hosts for the parasite Oliva et al, 2008). For example, female E. analoga infested with epibiotic algae have reduced burrowing speeds, and are more likely to be preyed upon by birds as a consequence (Firstater et al, 2009;Hidalgo et al, 2010). Although the negative effect of parasite infection on burrowing speed was not large, it may nonetheless cause meaningful differences in predation risk because the crabs burrow incredibly quickly (MacGinitie, 1938) and because predatory birds, including definitive hosts for P. altmani, sometimes visually locate crabs prior to attempting to capture them (Blokpoel et al, 1992), and are less successful at capturing buried crabs than crabs that are at or near the surface (Ryan et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Epizoic growth on contemporary crustaceans has been shown to decrease swimming or burrowing capabilities and can even lead to significantly increased casualties from predation (e.g. Bauer, 1981;Hidalgo et al, 2010). Grooming, i.e., preening and cleaning of various parts of the body involving secondary modification of locomotory or feeding appendages, is a frequent and important strategy adopted by a range of crustaceans (Bauer, 2013).…”
Section: Epizoic Growthmentioning
confidence: 99%
“…Another dynamic that is not explored here is the potential to increase or decrease predation. Past research on the crab Emerita analoga found that algal epibiont growth increased predation possibly due to negative effects on burrowing time and increased visualization by predators [22].…”
Section: Environmental Variation Leads To Variation In Epibiontmentioning
confidence: 99%